Acido, ergo sum: Holger Hydén – the neuroscientist in Cortázar's Hopscotch Acido, ergo sum: Holger Hydén – o neurocientista em O Jogo da Amarelinha, de Cortázar - Guillermo Delgado; Bruno Estañol (Arquivos de Neuro-Psiquiatria)
The fictional Italian author Morelli is throughout the novel “Hopscotch” (1963) Julio Cortázar's alter ego. This character proposes an unoriginal literary hypothesis in chapter 62. There is an allusion to a particular Swedish that ‘is working on a chemical theory of thought.’ The Swedish neuroscientist under analysis is Holger Hydén (1917-2000), by then professor and chairman of the Department of Histology at the University of Göteborg. Hydén, who was the first to work in neurobiological micromethods, is mentioned by Morelli due to his participation in a symposium held at the end of January 1961, in San Francisco. His pioneering work will never be completely forgotten, because Hydén's neuroscientific legacy lives and will live in Cortázar's “Hopscotch”. O autor italiano de ficção Morelli atua, no romance “Jogo da Amarelinha” (1963), como o alter ego de Julio Cortázar. Este personagem propõe uma hipótese literária sem originalidade no capítulo 62. Há uma alusão a um sueco em particular que “está trabalhando em uma teoria química do pensamento”. O neurocientista sueco em questão é Holger Hydén (1917-2000), então professor e diretor do Departamento de Histologia da Universidade de Gotemburgo. Hydén, que foi o primeiro no uso de métodos para a microdissecção de neurônios individuais, é mencionado por Morelli devido a sua participação em um simpósio realizado em São Francisco, no final de janeiro de 1961. Seu trabalho pioneiro nunca será esquecido completamente porque seu legado neurocientífico vive e vai viver em “Jogo da Amarelinha”, de Cortázar.